Within-subject, double-blind, human laboratory examination of opioid response profiles in males and females across three harmonized studies - LeComte, Robert; Brown, Nicole; Davis, William; Pattillo, Emma; Ellis, Jennifer D.; Huhn, Andrew S.; Campbell, Claudia M.; Finan, Patrick H.; Bergeria, Cecilia L.; Dunn, Kelly E. (Drug and alcohol dependence, 2025)
Opioid use disorder (OUD) poses significant individual and public health challenges and understanding whether opioids engender different effects in patient samples is imperative to determining unique risk factors for developing OUD. These analyses examined whether participant sex was associated with different experiences of opioids. Participants with little or no prior opioid experience (N = 160) were enrolled into one of three randomized, double-blind, placebo-controlled human laboratory studies that were harmonized together for these analyses. The effects of the opioid agonist hydromorphone (4mg, oral) and placebo were compared in males and females as a first step towards determining how demographic characteristics may be associated with different opioid response profiles. Data included self-report ratings, staff observed ratings, and physiological responses. Results found hydromorphone produced expected self-reported and observed agonist effects with few differences. Females reported more energy and were more talkative for a short period after dosing, but then reported and were observed as being sleepy for the rest of the session, whereas males reported more energy that was sustained throughout the session. No interactions between sex and drug were observed. Altogether, these data provide evidence that among persons who had little to no prior experience with opioids, sex did not meaningfully predict different response profiles to the dose of hydromorphone. These findings may serve as the basis for future studies examining sex differences in the onset of other SUDs, later stages of SUDs, and overall trajectories of SUDs. •Opioid use disorder (OUD) poses significant individual and public health challenges.•Evaluating differential effects of opioids in patient samples is imperative to determining unique risks for developing OUD.•Analyzing effects in men and women is a first step toward determining how sex relates to opioid response profiles.•Data suggest that sex may not meaningfully predict response profiles in persons with little to no prior opioid experience.